Economic globalization and economic performance nexus: Does the moderating role of governance matter? - Nkemdilim Iheanachor; Azuka Elvis Ozegbe (International Journal of Management, Economics and Social Sciences (IJMESS), 2023)
This inquiry was inspired by the quest to examine the interaction effects of economic globalization and governance on the performance of the Nigerian economy from 1996 to 2021. The study employed the modern Autoregressive Distributed Lag Model (ARDL) approach to analyze the annual time-series data obtained from the World Bank Development indicators (WDI) and the KOF institute. Based on the estimated results, the empirical findings indicate that changes in economic globalization and governance exerted a positive and statistically significant long-run impact on Nigeria's economic performance. Consequently, the interaction between economic globalization and governance had a positive and significant long-run effect on the nation's economic performance. The foregoing suggests that governance is a significant moderating factor between economic globalization and economic performance. From the purview of policy formulation, the findings call on the government to continue to strengthen institutional quality in order to fully harvest the benefits of economic globalization in its quest to attain sustainable economic development.
Keywords: C32; F02; F43; E01; G30; Q01; 330; Globalization; governance; economic performance; autoregressive distributed lag; foreign investment